Rehabilitation for hydrocephalic children - (:unkn) unknown (Springer International Publishing, 2019)
Hydrocephalus developing by the accumulation of an excessive amount of cerebrospinal fluid in the ventricles and/or subarachnoid space in infants or children can cause many problems that require rehabilitation. Especially in this period, frequently encountered highpressure hydrocephalus can create problems regarding physical development depending on the motor system, achievement of milestones, balance, coordination, and mobility. The accompanying cognitive impairment, epilepsy, sensory deficits, and endocrine dysfunctions make the situation worse. If motor problems aren't dealt with the other morbidities, serious school and social integration difficulties can occur, and this impairs the life quality of both the patient and his/her family significantly. © Springer Nature Switzerland AG 2019. All rights reserved.
Keywords: Children; Hydrocephalus; Management; Outcome; Rehabilitation